PENGAWASAN PEREDARAN MAKANAN KADALUARSA OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI PEKANBARU - Zira Arissafitri; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Circulation of expired food products is still a big problem for Pekanbaru City. This study was conducted to determine the supervision carried out by the Center for Drug and Food Control in Pekanbaru on the circulation of expired food products in Pekanbaru City. The research was conducted using qualitative methods with descriptive research type. This study uses Manullang's theory of supervision by setting standard measuring instruments, conducting assessments and taking corrective actions. In this study, the data collection techniques used were observation, interviews and documentation. These results indicate that the supervision of the circulation of expired food by the Food and Drug Supervisory Center in Pekanbaru is still not going well due to the lack of guidance to business actors and the public, legal sanctions that have not been firm, the number of employees and the number of operational vehicles, and the lack of community participation. in monitoring the circulation of expired food products in Pekanbaru City. Therefore, in the context of optimizing the supervision of the circulation of expired food by the Center for Drug and Food Control in Pekanbaru, it is necessary to improve guidance for business actors and the public, provide strict legal sanctions, increase the number of human resources and increase the number of operational vehicles. Keywords: Supervision, Distribution Facilities, BBPOM